2011
DOI: 10.1002/lt.22354
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B immunoglobulin and/or nucleos(t)ide analogues for prophylaxis against hepatitis b virus recurrence after liver transplantation: A systematic review

Abstract: A combination of hepatitis B immunoglobulin (HBIG) and nucleos(t)ide analogues (NUCs) is currently recommended as prophylaxis against the recurrence of hepatitis B virus (HBV) after liver transplantation (LT), but the optimal protocol is a matter of controversy. The aim of this study was the identification of factors associated with post-LT HBV recurrence in patients receiving HBIG and NUCs. We searched MEDLINE and PubMed for studies in English about the effectiveness of HBIG and NUCs [lamivudine (LAM) and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 67 publications
(514 reference statements)
2
90
1
3
Order By: Relevance
“…28 This can be largely attributed to the greatly reduced recurrence rate of hepatitis after liver transplant in patients with HBV infection after the introduction of prophylactic therapy in the form of either lamivudine and hepatitis B immunoglobulin or entecavir and hepatitis B immunoglobulin. 9,21,[32][33][34][35] We found significantly low patient and graft survival in patients with both HBV and HCV in our study; this finding is similar to the results of Waki and associates, 36 who analyzed data from the United Network for Organ Sharing for liver graft survival in patients with different types of viral hepatitis and found that recipients with HBV had the highest graft survival compared with patients with HCV infection or patients with combined HBV and HCV. In our study, we only had 5 patients with combined HBV and HCV; all of these patients had fulminant hepatic failure and 4 had concomitant HCC, which resulted in worse prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…28 This can be largely attributed to the greatly reduced recurrence rate of hepatitis after liver transplant in patients with HBV infection after the introduction of prophylactic therapy in the form of either lamivudine and hepatitis B immunoglobulin or entecavir and hepatitis B immunoglobulin. 9,21,[32][33][34][35] We found significantly low patient and graft survival in patients with both HBV and HCV in our study; this finding is similar to the results of Waki and associates, 36 who analyzed data from the United Network for Organ Sharing for liver graft survival in patients with different types of viral hepatitis and found that recipients with HBV had the highest graft survival compared with patients with HCV infection or patients with combined HBV and HCV. In our study, we only had 5 patients with combined HBV and HCV; all of these patients had fulminant hepatic failure and 4 had concomitant HCC, which resulted in worse prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…The combination prophylaxis with antiviral agents and HBIG reduces the HBV recurrence rate to 5% at 5 years, which is now almost universally adopted by most transplant centers as the golden standard for the prevention of HBV reinfection. 4 However, passive immune prophylaxis with long-term administration of HBIG is associated with many issues, including the limited availability of HBIG, possible emergence of HBV envelope protein mutations, 5 development of resistance to nucleotide analogs 6 and, especially, extremely high costs. 7 The ideal prophylactic strategy is to stop prophylaxis with HBIG when HBV infection had been completely cleared.…”
Section: Introductionmentioning
confidence: 99%
“…Although nucleoside analogues are useful for preventing hepatitis B recurrence, the recurrence rate was lowest in patients who received combined hepatitis B immunoglobulin plus nucleoside analogue prophylaxis (6.6 %) compared with those receiving nucleoside analogue prophylaxis alone (19.0 %) or hepatitis B immunoglobulin prophylaxis alone (26.2 %) [234]. The combination of hepatitis B immunoglobulin and ADV was more effective than hepatitis B immunoglobulin plus LDV prophylaxis [234].…”
Section: Portal Vein Thrombosismentioning
confidence: 95%